Antibody-based prevention of von Willebrand factor degradation mediated by circulatory assist devices - Rauch, Antoine; Legendre, Paulette; Christophe, Olivier D.; Goudemand, Jenny; Belle, Eric van; Vincentelli, André; Denis, Cécile V.; Susen, Sophie; Lenting, Peter J. (Thrombosis and Haemostasis, 2014)
Haemorrhagic episodes in patients carrying circulatory assist devices represent a severe life-threatening clinical complication. These bleeding episodes may originate from a reduced functionality of von Willebrand factor (VWF), a multimeric protein pertinent to the formation of a haemostatic plug. It has been reported that the reduced functionality is due to increased proteolytic degradation by the enzyme ADAMTS13, a phenomenon that is facilitated by device-induced increases in shear stress to which VWF is exposed. Here, we have tested a series of VWF-derived protein fragments and monoclonal murine anti-VWF antibodies for their capacity to reduce shear stress-dependent degradation of VWF. Via direct binding experiments, we identified an anti-VWF antibody that partially blocked VWF-ADAMTS13 interactions (46 ± 14%). Epitope mapping experiments revealed that the antibody, designated mAb508, is directed against the distal portion of the VWF D4-domain (residues 2134–2301) and recognises a synthetic peptide encompassing residues 2158–2169. Consistent with its partial inhibition of VWF-ADAMTS13 interactions in binding assays, mAb508 reduced ADAMTS13-mediated VWF degradation in a vortex-based degradation assay by 48 ± 10%. In a HeartMateII-based whole bloodperfusion system, mAb508 was able to reduce degradation of highmolecular- weight (HMW)-VWF-multimers dose-dependently, with a maximal inhibition (83 ± 8%) being reached at concentrations of 10 μg/ml or higher. In conclusion, we report that partial inhibition of VWF-ADAMTS13 interactions using an anti-VWF antibody can prevent excessive degradation of HMW-VWF multimers. This strategy may be used for the development of therapeutic options to treat bleeding episodes due to shear stress-dependent VWF degradation, for instance in patients carrying circulatory assist devices.
Keywords: von Willebrand factor; ADAMTS13; circulatory assist devices; acquired von Willebrand syndrome; antibody therapy